Network pharmacology prediction and molecular docking analysis on the mechanism of eugenol as a candidate against estrogen receptor-positive breast cancer - Irene Natalia Nesta Sihombing; Ade Arsianti (GarVal Editorial Ltda., 2024)
Context: Breast cancer therapy currently presents several uncomfortable side effects in patients, including effects on non-malignant tissues, recurrence, and resistance, which restrict their utilization. Consequently, researchers have directed their attention toward studying plant-derived anticancer compounds that exhibit high efficacy and safety profiles. Eugenol, a major component found in clove plants, demonstrates promising potential as a therapeutic agent for both estrogen receptor-positive and estrogen receptor-negative breast cancer. Aims: To predict the target of eugenol in estrogen receptor-positive breast cancer using network pharmacology and molecular docking analyses. Methods: Network pharmacology analysis was performed using the Chemical Toxigenomic Database, STITCH, GeneCards, Cytoscape, Enrichr, and Stringdb. Subsequently, molecular docking was performed using protein targets obtained from the RCSB-PDB and analyzed using AutoDock software. Results: Network pharmacology study and molecular docking revealed the anticancer effect of eugenol against breast cancer estrogen receptor-positive, especially in cancer and apoptotic pathways, by acting on caspase-3 (CASP3), epidermal growth factor receptor (EGFR), and poly [ADP-ribose] polymerase 1 (PARP1) signaling pathways. The docking results between the protein targets and eugenol showed that eugenol has the strongest binding with CASP3 (ligand binding energy: -5.78 kcal/mol), followed by eugenol binding with EGFR (ligand binding energy: -5.58 kcal/mol), and eugenol binding with PARP1 (ligand binding energy: -5.58 kcal/mol). Conclusions: Eugenol is a potential candidate for breast cancer therapy, especially for apoptosis mediated by CASP3 in breast cancer luminal A.